Robust GPS Carrier Tracking Model Using Unscented Kalman Filter for a Dynamic Vehicular Communication Channel - Jiachen Yin; Rajesh Tiwari; Martin Johnston (IEEE Access, 2018)
The carrier tracking loop in a GPS receiver is considered to be an important process but also a weak link since the loss of signal lock can occur in a variety of situations. Low carrier-to-noise ratios and highly dynamic environments are common scenarios for a vehicular communication channel when random phase fluctuations in a dynamic environment are common. We propose a novel and robust carrier tracking approach by dynamically integrating an adaptive unscented Kalman filter assisted by a third-order phase lock loop in order to improve the robustness of tracking capability and accuracy in dense and dynamic environments. Experiments are conducted to investigate the tracking performance of the proposed carrier tracking approach and compare it with existing algorithms for generic GPS receiver. Results indicate that the proposed approach has a better performance in tracking capability and tracking accuracy in highly dynamic environments, and the proposed method achieves a better performance on vehicular communication channels.